Assistance in the Formulation and Preparation of the Curriculum at Bimba Rainbow Kids Al-Ghifary Cibungbulang Bogor - Fuad Ahmad Riva’i; Muhammad Arif Kurniawan; Syafira Aulia (al-Afkar, Journal For Islamic Studies, 2024)
The curriculum is the most important component in an educational process, education will not be able to run well without a good curriculum. Therefore the curriculum must be designed and structured in such a way as to achieve the expected educational goals. As for what is meant by the curriculum here is a set of plans that contain objectives, learning materials, and methods used as guidelines in organizing the learning process to achieve predetermined educational goals. This community service activity is carried out to provide assistance and guidance to schools in order to compile and formulate the curriculum so that it becomes a systematic curriculum document that serves as a learning guide for teachers at the school. This community service uses techniques and methods in the form of assistance and guidance carried out in stages by involving all school components, namely principals, teachers and education personnel. From the mentoring and guidance activities that have been carried out, it can be concluded that community service activities in the form of mentoring have run well and successfully. This is evidenced by the compilation of the book one curriculum document at the early childhood education level at the biMBA (guidance of Children's Interest and Reading) educational institution.